Assessment of Validity of Pont’s Index and Establishment of Regression Equation to Predict Arch Width in Nepalese Sample - Dhakal, Jyoti; Shrestha, Rabindra Man; Pyakurel, Ujjwal (Orthodontic Journal of Nepal, 2014)
Objective: To evaluate the validity of Pont’s index in Nepalese population and establish the regression equation to predictprobable arch width from sum of the maxillary incisors. Materials & Method: The sample comprised of 50 female and 50 male subjects of the age ranging 17-24 years. Sum of themesio-distal widths of the maxillary incisors were measured. Descriptive statistics, Coefficient of regression, and regressionequation were calculated to predict the arch width in premolar and molar regions. Independent t-test was performed to findthe difference between mean values of male and female subjects. Statistical analysis was done using SPSS version 17.0. Result: Mean value of Pont’s index ratio was 0.80 and 0.63 for premolar and molar respectively for Nepalese sample. Statisticalanalysis showed no significant difference between male and female in Pont’s premolar and molar index. The correlation ofcoefficient for Sum of Incisors/Premolar width and Sum of Incisors/Molar width were 0.39 and 0.46 respectively. Conclusion: Pont’s analysis can be applied in Nepalese samples. There is no significant difference in values between male andfemale samples. DOI: http://dx.doi.org/10.3126/ojn.v4i1.11305 Orthodontic Journal of Nepal Vol.4(1) 2014; 12-16